Home-leaving decisions of daughters and sons - Maria Concetta Chiuri; Daniela Del Boca (Institute for the Study of Labor (IZA), 2010)
In spite of relevant differences between countries, a common international pattern emerges: daughters leave parental homes earlier than sons. Drawing upon the European Community Household Panel, we explore the impacts of various factors that affect daughters' and sons' home-leaving decisions. Our results show important differences across genders as well as across countries. The decisions of daughters appear to be more responsive than sons' to family structure as well as to institutional factors such as the labor and the mortgage market.
Keywords: J2; C3; D1; 330; Living arrangements; gender; social policies; Jugendliche; Wohnungswechsel; Geschlecht; Familiensoziologie; Vergleich; EU-Staaten